Epidemiology of Epilepsy in Lubumbashi, Democratic Republic of Congo - Olivier Mukuku; Pascal Nawej; Marcellin Bugeme; Frank Nduu; Paul Makan Mawaw; Oscar Numbi Luboya (Neurology Research International)
Background. Epilepsy is one of the most common neurological conditions, but the majority of epilepsy patients in sub-Saharan countries do not receive appropriate treatment. In the Democratic Republic of Congo (DRC), particularly in Lubumbashi, very few epidemiological studies on epilepsy have emerged. This study aims to analyze demographic characteristics, semiology of epileptic seizures, and their etiologies in patients followed in hospital. Methods. This is a prospective descriptive study that enrolled 177 epileptic patients who performed a neurological consultation at the Centre Médical du Centre Ville (CMDC) in Lubumbashi (DRC) from January 1, 2016, to December 31, 2017. Results. The mean age of the patients was 20.0 years (range: 5 months and 86 years). The male sex was predominant (57.1%). The mean age at the seizure onset was 13.1 years, and the mean duration between onset of seizures and consultation was 83.5 months. The family history of epilepsy was present in 27.7%. Generalized tonic-clonic seizures were the most frequent (58.2%), followed by atonic generalized seizures (9.6%) and focal clonic seizures (8.5%). The etiology was found in 68 (38.4%) patients and was dominated by neurocysticercosis (26.5%), meningitis (25%), perinatal pathologies (20.6%), and head injury (20.6%). Conclusion. This study is a useful starting point from which health programs and health professionals can work to improve the diagnosis and quality of epilepsy management in our community.